PENGARUH DIVERSITAS DEWAN DIREKSI TERHADAP NILAI PERUSAHAAN - Saputra, Wendy Salim (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The establishment of a company has a clear purpose. The company's goal is to achieve maximum profits and prosper the owner of the company or the shareholders (stockholders). One of the reasons why companies in Indonesia are vulnerable to economic turmoil is the weak implementation of good corporate governance. Good Corporate Governance (GCG) is basically a concept that concerns the company's structure, division of tasks, division of authority, division of responsibilities of each element of the company structure. The purpose of this study is to determine the influence of the female board of directors, the age of the board of directors, educational background of the board of directors, and the board of directors of foreign nationality towards the value of the company in LQ45 companies listed on the Indonesia Stock Exchange in the period 2015-2017. The research method used in this study is a hypothesis test that is to analyze the influence of the female board of directors, the age of the board of directors, the educational background of the board of directors, and the foreign board of directors of corporate value. Based on the data obtained, the results of the educational background variables of the Board of Directors and foreign board of directors influence the value of the company, while the variable of the board of directors of women and the age of the board of directors do not affect the value of the company. Keywords: Gender, Age, Education, Nationality, Firm Value